Communication and public participation in environmental decision making - Depoe, Stephen P., 1959-; Delicath, John W.; Elsenbeer, Marie-France Aepli (SUNY series in communication studies., 2004)
"The contributors to this volume explore the communication practices of various stakeholders - interested citizens, grassroots and public interest groups, industry representatives, scientists and technical experts, government agencies, federal regulators - engaged in a variety of environmental decision-making contexts in the U.S. and elsewhere. Included are case studies that analyze individuals and organizations participating both within institutional mechanisms and through alternative forms of environmental advocacy